Effects of Heterogeneous Weak Perpendicular Homogeneous Permanent Magnetic Field and Mechanical Polishing on Corrosion Behavior of the Surface of Aluminum Sand Cast Alloy AlSi10Cu(Fe) in Contact with Sand - Belkacem Korichi; Hadj Ali, Youcef; Zazi, Nacer; Aouchiche, Hocine; Chopart, Jean Paul (Protection of Metals and Physical Chemistry of Surfaces, 2025)
We have analyzed the corrosion behavior of the AlSi10Cu(Fe) aluminum cast alloy of the surface in contact with sand during the casting, before and after polishing with and without perpendicular heterogeneous weak permanent magnetic field. The results obtained show that after immersion of non-polished sample generalized corrosion appears and the formation of hillocks on certain ridges of the microstructure were observed, and there is electrochemical noise only during 35 s of immersion of the sample; after that, fluctuations of stair steps take place. The polishing induces localized corrosion, pitting corrosion, and non-perfect-shape electrochemical noise until 24 h of immersion. It was observed that the application of a perpendicular homogeneous weak permanent magnetic field to the polished sample made the shape of the electrochemical noise perfect in the first 10 min, but after 24 h, the fluctuations took the form of stair steps.
Keywords: AlSi10Cu(Fe) aluminum cast alloy; corrosion; electrochemical noise; heterogeneous weak magnetic field; surface in contact of sand